Eremophilane sesquiterpenoids from the endophytic fungus Curvularia lunata BCC76963. (21st March 2023) - Sadorn, Karoon; Saepua, Siriporn; Boonyuen, Nattawut; Auncharoen, Patchanee; Rachtawee, Pranee; Pittayakhajonwut, Pattama
Abstract: A chemical investigation on broth and mycelia extracts of the endophytic fungus Curvularia lunata BCC76963 led to the isolation of five new eremophilane sesquiterpenoids, curvuleremophilanes A−D (1 –4 ) and septeremophilane I (5 ), one new conjugated unsaturated fatty acid, (6 S, 2 E, 4 E )-8-hydroxy-4, 6-dimethylocta-2, 4-dienoic acid (6 ), and one new phenylacetic acid derivative, 4′-chlorocurvulin (8 ), along with ten known compounds. The chemical structures were elucidated based on the analyses of HRESIMS and NMR spectroscopic data. The absolute configurations of eremophilanes were assigned by the evidence from NOESY correlations, chemical conversion, optical rotation values, and ECD spectroscopic data in conjunction with biogenetic considerations. In addition, the absolute stereochemistry of compound 5 was confirmed by X-ray crystallography. Curvuleremophilane A (1 ), dendryphiellin I (10 ), chaetopenoid B (11 ), and bipolaroxin (12 ) displayed antimalarial activity against Plasmodium falciparum K1 with IC50 values in a range of 3.64–7.77 μM and antibacterial activity against Bacillus cereus and Staphylococcus aureus with MIC values in a range of 3.13–12.50 and 1.56–25.00 μg/mL, respectively. These compounds, except for compound 11, also showed cytotoxicity against NCI-H187 and Vero cells with respective IC50 values in a range of 2.76–3.97 and 2.34–4.67 μM. Graphical abstract: Image 1 Highlights: Five new eremophilanes were isolated from Curvularia lunata BCC76963. The structures were elucidated by spectroscopic evidence and chemical conversions. The absolute configuration of septeremophilane I was confirmed by X-ray crystallography. Curvuleremophilane A showed antimalarial, antibacterial, and cytotoxic activities.